Inconsistências no cumprimento da Convenção das Nações Unidas contra a corrupção (Convenção de Mérida) pelo Estado brasileiro - Santos, Érika Karine (2024)
The inconsistencies in the Brazilian State's compliance with the United Nations Convention against Corruption (Merida Convention) can be analyzed through a critical examination of the divergences between Brazil's legal and legislative practices and, even more so, the commitments assumed through this international agreement. In this context, issues related to the intrinsic challenges of the national legal and political system are addressed, as well as the demands for more integral and transparent governance, further specifying the theme. Thus, it becomes evident that the problem of the theme revolves around the following question: how can Brazil overcome these inconsistencies to effectively comply with the Mérida Convention? The study of the chosen theme is important because it has significant consequences for the social, economic, and legal reality of the country, highlighting the need to improve the fight against corruption and strengthen governance. Among the difficulties pointed out, the objective is to uncover the existing incongruities and identify viable paths to eliminate these discrepancies, thereby reinforcing the efforts to combat corruption within the national territory. As methodological procedures applied research is used, with an inductive method, theoretical type, exploratory and descriptive objectives, qualitative approach, and bibliographic and documentary technical procedure. It is concluded that it is essential for Brazil to overcome inconsistencies and effectively comply with the Mérida Convention by adopting strategic measures and structural reforms, involving the strengthening of international cooperation mechanisms, improvement of mutual legal assistance processes in criminal matters and extradition, promotion of efforts integration in tracking and recovering illicit assets, and carrying out legislative reforms that align national legislation with the international standards established conventionally.